Investigating Students’ Perception Using Audio-Visual Material in Listening Class - Rahma Fitria; Iswahyuni Iswahyuni; Widya Caterine Perdhani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Listening comprehension is one of the most difficult English language skills for learners. Since listening is an important part of communication, as foreign learners we should acquire listening skills. However, learning listening is lack motivation and most students find difficulties in learning listening. To support learners in learning listening is needed an appropriate medium that facilitates learners in improving their listening comprehension skills. This study aimed to investigate students' perceptions using audio-visual material as a media in listening class. A survey study using a quantitative approach was designed to collect the data. The researcher used a survey questionnaire with 20 Likert Scale questions and distributed them through Google Forms. The sample of this study is 9th-grade students from SMP Shalahuddin in total 109 students from classes A, B, C, and D. After collected the data, the researcher analyzes the data using SPSS. The result shows that students had positive experiences in using audio-visual material in listening class. Most of the students agree that audio visual is interesting, motivating, and entertaining them. Audio-visual also can help students to improve their listening comprehension. However, they find difficulties when the speaker speaks too fast, the speaker explains unfamiliar material or uses unfamiliar accents, and pronunciation.